THE ROLE OF LIVE STREAMING ELEMENTS IN INFLUENCING CONSUMER PURCHASE BEHAVIOR: A SYSTEMATIC LITERATURE REVIEW OF THE FITNESS PRODUCT MARKET - Gu, Yingying; Nazarudin, Mohamad Nizam; Mazalan, Nur Shakila (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
The rise of live streaming has redefined digital marketing, particularly in the fitness industry, where real-time interactions between influencers and consumers shape purchasing decisions. This systematic literature review (SLR) explores how elements within live streaming, specifically streamer characteristics, fitness product properties, and the streaming environment, influence consumer perceptions of trust, perceived value, and ultimately, purchase behaviour. Conducted through a comprehensive search of academic databases, this review includes 50 studies published between 2015 and 2024. The review synthesizes findings to offer insights into how streamer credibility, product quality, and interactivity drive consumer engagement. This study provides a cohesive understanding of the mechanisms at play in live streaming and offers recommendations for future research to deepen our understanding of digital consumer behaviour in this context.